Mpox diagnostics: Review of current and emerging technologies. Issue 1 (3rd January 2023) - Lim, Chuan Kok; Roberts, Jason; Moso, Michael; Liew, Kwee Chin; Taouk, Mona L.; Williams, Eloise; Tran, Thomas; Steinig, Eike; Caly, Leon; Williamson, Deborah Ann
Abstract: Mpox is a zoonotic disease caused by monkeypox virus (MPXV) from the Orthopoxvirus genus. Unprecedented transmission events have led to more than 70 000 cases reported worldwide by October 2022. The change in mpox epidemiology has raised concerns of its ability to establish endemicity beyond its traditional geographical locations. In this review, we discuss the current understanding of mpox virology and viral dynamics that are relevant to mpox diagnostics. A synopsis of the traditional and emerging laboratory technologies useful for MPXV detection and in guiding "elimination" strategies is outlined in this review. Importantly, development in MPXV genomics has rapidly advanced our understanding of the role of viral evolution and adaptation in the current outbreak.